HUMAN EXISTENCE IN THE POEM "MUKHODH LIL WILADAH FI AL AKHDHARAR" - Agesta Nurul Fauziyah; Abdul Muntaqim Al Anshory (Journal of Arabic Literature (JaLi), 2023)
Poetry is a type of literature that's more than just words on a page; it carries deep significance. One way to understand the meaning of poetry is by applying Riffaterre's semiotic theory as an analytical tool. Michael Riffaterre’s theory of semiotic poetry analysis highlights the need to focus on a poem’s language structure and elements. This approach helps to comprehend the overall meaning of the poem in three steps. The aim of this study is to understand the heuristic and hermeneutic reading process as well as identify instances of discontinuous expression in the poem "Mukhodh Lil Wiladah Fi Al Akhdharar.". This study is qualitative descriptive research that uses Michael Riffaterre's theory as a conceptual framework for analyzing poetry as a source of data. The method of analysis employed in this study is the technique developed by Mills and Humberman. The heuristic and hermeneutic analyses reveal that the poem "Mukhodh lil wiladah fi al akhdhahrar" by Ahmad Binmaimun broadly addresses matters related to life and humanitarian concerns. In the heuristic reading, the poem largely reflects the author's fascination with the concept of birth. Generally, the hermeneutic interpretation of Ahmad bin Maimun's poem "Mukhadh lil wiladah fi al akhdhahrar" conveys life's meaning and is rich with metaphorical language about human existence. The writer aims to communicate to the reader a profound desire to experience rebirth. Fueled by dreams and unwavering resolve, the writer expresses readiness to rise once more, striving to enhance all conditions for the better. The discontinuity of expression indicates that there are 13 instances of word meaning substitution, including 3 similes, 3 metaphors, 2 instances of personification, 1 allegory, 1 synecdoche, 2 metonymies, and 1 epic parable. As for the deviation of meaning, it includes 1 ambiguity, 1 contradiction, and 1 nonsensical expression. In terms of meaning creation, there is 1 instance of enjambement.